The Concept of Land Bank Agency: Between Public or Bussiness Functions? - Anak Agung Gede Duwira Hadi Santosa; I Made Marta Wijaya; Ni Luh Dewi Sundariwati; Made Dwita Martha (Varia Justicia, 2022)
The concept of a Land Bank entity in the Job Creation Act and its derivative regulations reflects the contradictory dualism of the functions of the Land Bank agency. On the one hand, the Land Bank agency was formed to carry out public functions, but on the other hand, the Land Bank could carry out business activities. The existence of this dualism results in ambiguity and imbalance in the functions of the Land Bank agency. This research aims to examine the concept of a Land Bank entity as contained in the Job Creation Law and its derivative rules and to provide an overview of the model of a Land Bank entity in the future that can balance the implementation of public and business functions. The research used normative legal research supported by the statutory approach and a conceptual approach. The results show that the concept of a Land Bank agency in the Job Creation Law and its derivative rules still reflects the dualism of contradictory functions of the Land Bank agency, namely as executor of public functions and as executor of business activities. It is necessary to revamp the concept of the Land Bank agency to avoid conflicts of interest between public and private scope, by dividing the Land Bank entity into two types, which is the Land Bank entity in the form of public legal entity and/or private legal entity.